Research on the Integrated Detection Host System of Urban Rail Transit Trains - CHEN Zhi; LYU Hongqiang (Chengshi guidao jiaotong yanjiu)
［Objective］ In order to ensure the safe operation of urban rail transit, meet the detection requirements of track obstacles and key components such as pantograph-catenary, running gear and track, and solve problems of the detection subsystems independent of each other and the vehicle integration redundancy, it is necessary to conduct research on the integrated detection host system of trains. ［Method］ The subsystems of the active obstacle detection, pantograph-catenary detection, running gear detection, and track geometry dynamic detection are designed in an integrated way, and an integrated detection host system is proposed. Specifically, the active obstacle detection subsystem is directly connected to the AI (artificial intelligence) board of the integrated host through a switch, and each of other subsystems is first connected to a front-end host for data preprocessing, and then connected to the AI board of the integrated host through a switch. ［Result & Conclusion］ The proposed system can monitor the real-time running status and operating environment of the train, promptly detect potential safety hazards and issue early warnings, thus providing guarantees for the safe operation of urban rail transit. Compared with other existing independent detection subsystems, the proposed one breaks down the barriers between detection subsystems and simplifies the vehicle integration. It can alleviate the on-board equipment redundancy, save the overall power consumption of the train, reduce system costs, ultimately improving system compatibility and extensibility, as well as the efficiency of system configuration, maintenance and monitoring.